The effects of ractopamine-HCl (Optaflexx) on finishing feedlot heifers - M.J. Quinn; E.R. Loe; M.E. Corrigan; James S. Drouillard; Brandon E. Depenbusch (Kansas Agricultural Experiment Station Research Reports, 2007)
Whether occurring naturally or synthetically, beta-agonists are classified as phenethanolamines based on their chemical structure. Other specificities of structure determine the exact behavior of the compound in animals. Beta-agonists bind to specific receptors on the cell membranes of skeletal muscle, adipose,and other tissues. Upon binding, these agents alter metabolic pathways, ultimately causing a repartitioning of nutrients to increase muscle and decrease fat accretion. In cattle, betaagonists such as cimaterol and clenbuterol improve feed efficiency, average daily gain, and longissimus muscle area. The proposed effects of ractopamine HCl are similar to those of other beta-agonists. The purpose of this study was to examine the effects of ractopamine-HCl on live performance, carcass characteristics, and meat quality of finishing beef heifers.
Keywords: Cattlemen' s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Beta-agonists; Ractopamine-HCl